SOSIALISASI DAN FGD DI PULAU HIRI MALUKU UTARA - Mahdi Tamrin; Sabaruddin B (Universitas Mataram, 2025)
North Maluku is an archipelagic province located in eastern Indonesia. However, the majority of its population lives on small islands surrounding the island of Halmahera. One of the small islands with a significant population concentration is Hiri Island. Similar to the communities on Ternate Island and other small islands in North Maluku Province, the people here also engage in land conversion activities, transforming forest land into agricultural land as one form of adaptation. This community service activity was carried out using a collaborative and participatory approach, involving various stakeholders such as academics from Unkhair, KUPS Bukumanyeku, KPH Ternate Tidore, and BPDAS Akemalamo. The stages carried out were socialization, training, and evaluation of activities. The ecotourism socialization activity went well. Through the FGD (Focus Group Discussion) model, Hiri Island has ecotourism destinations such as beaches, mountains, and culture. Additionally, the island also faces challenges for further development, including the Ternate port, accommodations, and transportation. The presence of the KUPS Bukumanyeku organization is a significant asset for optimizing ecotourism on the island. Therefore, to address these challenges, collaboration among relevant stakeholders, particularly the Ternate City Government and the North Maluku Provincial Government, is required.